Creative Economy Literacy: Strategies for Improving Digital Entrepreneurship Competency for Millennials and Gen Z - Badar, Muhammad; Nasir, Muhammad; N, Normiyati; S, Herniah; Timur, Intan; Zulfaidah, Zulfaidah; Hajrah, Hajrah (Universitas Pejuang Republik Indonesia, 2025)
The creative economy has become a strategic sector in Indonesia's national economic development. This research and community service activity aims to develop and implement a creative economy literacy program that can improve digital entrepreneurship competencies for millennials and Gen Z. The method used is a mixed-method approach with a combination of participatory workshops, digital marketing training, business incubation, and continuous mentoring. The activity was carried out for six months involving 50 participants from students and young UMKM actors in Makassar City. Research instruments include creative economy literacy tests, digital entrepreneurship competency questionnaires, business activity observation sheets, and program impact evaluations. The results showed a significant increase in creative economy literacy by 78.5% from pre-test to post-test. Participants' digital marketing competency increased from 52.3% to 89.7%, while creative business management skills increased from 48.9% to 85.4%. This program successfully created 32 new creative startups with an average turnover of IDR 5.2 million per month in the first three months. This activity makes a real contribution to the development of the local creative economy ecosystem and can be replicated in other regions as a creativity-based economic empowerment model.